Deriva simulada de herbicidas em trigo - Zeni, Rodrigo (2021)
Wheat is one of the main winter cereals grown in southern Brazil. Different herbicides are used to control weeds in areas concomitant with wheat cultivation, including glyphosate and imazamox. In addition to the use of growth regulator, which is used to prevent crop lodging and express its productive potential. From this, drift or tank contamination can cause injuries to wheat, susceptible to these herbicides. Thus, the general objective of the research is to evaluate the impacts of underdoses of non-selective herbicides in interaction with growth regulators on the wheat crop. The objective of study I was to evaluate the effects of underdoses of glyphosate associated with the application of trinexapac-ethyl in two wheat cultivars. And the aim of study II was to evaluate the response of wheat to simulated imazamox drift at different phenological stages. The research was conducted in the field in the 2019 harvest, in which two experiments were carried out. In study I, the effect on physiological and productive parameters of the use of underdoses of glyphosate, associated or not with the use of TE growth regulator, in two wheat cultivars was evaluated. The results demonstrate the effect of simulated glyphosate drift increased phytotoxicity and reduced height, dry matter and yield of the wheat crop. The productivity of the Audaz cultivar was more affected by the increment of glyphosate subdoses, being reduced by 17 and 59% for the subdoses of 36 and 72 g ha-1, respectively (Figure 3B). The yield of cultivar Citrino remained unchanged up to the sub-dose of 36 g ha-1 of glyphosate, and with a maximum estimated loss of 34% in the sub-dose of 72 g ha-1. Phytotoxicity was more significant when associated with the use of trinexapac-ethyl, for both cultivars. Cultivar Audaz showed the greatest symptoms of phytotoxicity. In study II, the effect of using subdoses of imazamox at two stages of application in non-Clearfield wheat, evaluated in two locations, was studied. It was observed that the phytotoxicity caused by the simulated drift of imazamox was more pronounced in the tillering stage. Drift simulation by imazamox results in greater symptoms of phytotoxicity when applied in the tillering stage, especially in herbicide subdoses above 8.9% of the recommended dose. More studies are needed in order to know what is the real damage in other cultivars and times of underdoses of imazamox in susceptible cultivars.